Evaluation of the relationship between the range of radiation-induced lung injury on CT images after IMRT for stage I lung cancer and dosimetric parameters. (1st January 2021) - Itonaga, Tomohiro; Sugahara, Shinji; Mikami, Ryuji; Saito, Tatsuhiko; Yamada, Takafumi; Kurooka, Masahiko; Shiraishi, Sachika; Okubo, Mitsuru; Saito, Kazuhiro
Abstract: Background: This study evaluated the correlation between radiation-induced lung injury (RILI) and dosimetric parameters on computed tomography (CT) images of stage I non-small cell lung cancer (NSCLC) patients undergoing intensity-modulated radiotherapy (IMRT). Materials and methods: Sixty-three stage I NSLC patients who underwent IMRT were enrolled in the study. The patients underwent CT within 6 months (acute phase) and 1.5 years (late phase) after radiotherapy. These were fused with the planned irradiation CT. The range of RILI was measured from 10% to 100%, with an IC in 10% increments. Results: The median interval from completion of radiotherapy to acute and late phase CT was 92 and 440 days, respectively. The median RILI ranges of the acute and late phases were in the 80% (20–100%) and 70% dose regions (20–100%), respectively. The significantly narrower range of RILI when lung V20 in the acute phase was less than 19.2% and that of V5 in the late phase was less than 27.6% at the time of treatment planning. Conclusions: This study showed that RILI occurred in a localized range in stage I NSCLC patients who underwent IMRT. The range of RILI was correlated with V20 in the acute phase and V5 in the late phase. KEY MESSAGES: RILI correlated with V20 in acute and V5 in late phase. The shadow of RILI occurred in 80% dose region in acute and 70% in late phase. No relationship exists between radiographic changes in RILI and PTV volume.